An Effect of Sub-Surface Moisture Content on GPR Survey Performance - วิชาลัย ชนะรบ (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2019)
Performance of the Ground Penetrating Radar (GPR) depends on the wave reflectivity as shown as the amplitude height that varied with environmental conditions. Moisture content in sub-surface material has a large effect on signal attenuation. This research presents an effect of moisture content in asphaltic concrete road pavement and Concrete Treated Base (CTB) layers that would cause GPR signal to detection of water table. The simple methods to examine dielectric constant ( ) from two-way travel time of samples those collected from the field were tested in laboratory both dry and wet conditions. These test results were employed for time-to-depth conversion for GPR data interpretation and explanation of capillary effect that caused GPR results as it has difficulty to indicate groundwater table on the radar gram. The CTB sample was tested for rising of capillary force in the laboratory. However, GPR signal modelling was done to verify capillary effect on filed data and laboratory testing results. Study results found the dielectric constant of dry and wet asphaltic concrete samples are 7 and 20, respectively. The modelling of capillary test in 24 hrs indicate the capillary zone is height of 4.3 cm and GPR wave modelling shows reflectivity of GPR signal was reduced due to capillary effect.